2000
DOI: 10.1161/01.cir.101.19.2258
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms Responsible for Endothelial Dysfunction Associated With Acute Estrogen Deprivation in Normotensive Women

Abstract: Endothelial dysfunction secondary to acute endogenous estrogen deprivation is caused by reduced NO availability. Cyclooxygenase-dependent production of oxidative stress could be responsible for this alteration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
85
0
5

Year Published

2001
2001
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(98 citation statements)
references
References 54 publications
8
85
0
5
Order By: Relevance
“…In humans it has been suggested that the endothelial dysfunction secondary to acute endogenous estrogen deprivation (surgical ovariectomy) is caused by reduced NO availability, which results from COX-dependent production of oxidative stress (39).…”
Section: Oxidative Stress -Reactive Oxygen Speciesmentioning
confidence: 99%
“…In humans it has been suggested that the endothelial dysfunction secondary to acute endogenous estrogen deprivation (surgical ovariectomy) is caused by reduced NO availability, which results from COX-dependent production of oxidative stress (39).…”
Section: Oxidative Stress -Reactive Oxygen Speciesmentioning
confidence: 99%
“…Enhanced oxidative stress may be another factor contributing to this dysfunction, although controversy remains [66]. A recent study in normotensive women showed that endothelial dysfunction secondary to acute endogenous estrogen deprivation is strongly linked to a reduction in the bioavailability of ·NO [67]. Moreover, E 2 can attenuate O 2 −· formation in phagocytes [68] and endothelial cells [6].…”
Section: Discussionmentioning
confidence: 99%
“…De fato, a presença de receptores de estrogênio no coração, músculo liso vascular, no cérebro (núcleo do trato solitário e medula ventrolateral), as modificações na densidade de receptores adrenérgicos, nos níveis de AMPc e na NO sintase são sugestivas do possível envolvimento desse hormônio na regulação do sistema cardiovascular (Perrot-Applanat, 1996;Virdis et al, 2000). Estudos que demonstram diversas alterações ocorridas durante o ciclo estral normal, tais como intolerância ortostática, síncope, edema, variações de volume plasmático e alterações na regulação do sistema nervoso simpático dão suporte a essa participação (Thompson et al, 1988;De Souza et al, 1989;Hassan et al, 1990;Scott et al, 1990;Endicott J, 1993;Jacob et al, 1997;Jacob et al, 2000).…”
Section: Descritoresunclassified
“…Narkiewicz et al (2005) Além da ANSP, indivíduos com idade avançada parecem apresentar redução de fluxo sangüíneo e, portanto, aumento de resistência vascular (Moreau et al, 2002). De fato, essa variável parece estar diminuída com o envelhecimento, tanto em homens como em mulheres, sendo mediada tanto pela redução de oxido nítrico circulante quanto pelo aumento de secreção de endotelina (Dinenno et al, 1999;Virdis et al, 2000;Taddei et al, 2001). …”
Section: Envelhecimentounclassified
See 1 more Smart Citation